Friendly fire? : Negative campaigning among coalition partners - Haselmayer, Martin; Jenny, Marcelo (My University, 2018)
In democracies with multi-party competition, government parties face a dual challenge in election campaigns: on the one hand, they have to compete against and criticize their coalition partners. On the other hand, they should avoid virulent attacks on their partners to preserve their chances of future collaboration in government. Going beyond a dichotomous operationalization of negative campaigning, this manuscript analyses the tonality and volume of negative campaigning. Studying 3030 party press releases in four national Austrian election campaigns, different patterns for the tonality and frequency of negative campaigning reflect the electoral dilemma of government parties. Coalition parties criticize each other abundantly but refrain from ‘burning bridges’ with their partners through virulent attacks. These findings have implications for studying negative campaigning and coalition politics.
Keywords: Negative campaigning, multi-party competition, government coalitions, political parties, crowdcoding, campaign tonality; 320